How to Protect and Promote the Nutrition of Mothers and Children in Latin America and the Caribbean : Country Benchmarking - World Bank (World Bank, Washington, DC, 2016)
The study covered a wide range of topics, making data collection especially challenging. Key informants were sometimes new to their posts and were unable to provide details on specific programs, policies, or coverage rates. Few countries in Latin America and the Caribbean mainstream into their crisis and emergency plans protection of the nutritional status of mothers and children in the first 1,000 days of life. All countries should reinforce the promotion and protection of breastfeeding in emergencies, notably by providing an enabling space for mothers to safely breastfeed their children and by managing the provision of artificial milk formula. It is concerning that during emergencies most countries provide powdered artificial formula instead of ready-to-use artificial milk formula to infants that cannot breastfeed, greatly increasing the risks of illnesses and malnutrition as a result of inappropriate dilution and unsafe water. All countries need to reinforce their monitoring and evaluation systems, including surveillance of food and nutrition insecurity. While most countries have some form of monitoring system, few of those systems are computerized, which impairs timely and informed decision making. Systematic evaluations of emergency and crisis response are seldom performed. A number of countries would benefit from updating their nutrition policy and protocols based on the latest available evidence. Of particular importance are updates to the prevention and treatment of micronutrient deficiencies with micronutrient powders; treatment of acute malnutrition, notably with the use of ready-to-use supplements; and efficient treatment of diarrhea through the use of oral rehydration solution and zinc. Most countries will benefit from adapting the food and water rations given in emergencies to the specific nutritional needs of pregnant and lactating women and children <2 years of age.